Allowance for channel instability of passive synchronization system of time and frequency using geostationary satellites - Коваль, Ю.А.; Костыря, А.А.; Приймак, С.Ю.; Плехно, С.А.; Асаад, Х.Х. (Radiotekhnika, 2012)
Channel errors of the passive synchronization system of time and frequency caused by the nutation of geostationary satellites and irregularities ionospheric propagation delay of radio signals are considered. It has been possible to compensate significantly the satellite nutation action using the models of their daily movements. Famous models Klobuchar and IONEX are used for the introduction of ionospheric corrections.